Minimum Wages as a Redistributive Device in the Long Run - George Economides; Thomas Moutos (Center for Economic Studies and ifo Institute (CESifo), 2014)
This paper analyzes long run outcomes resulting from adopting a binding minimum wage in a neoclassical model with perfectly competitive labour markets and capital accumulation. The model distinguishes between workers of heterogeneous ability and capitalists who do all the saving, and it entails - relative to the perfectly competitive benchmark - large output and employment losses (among the lowest-ability workers) from the imposition of moderately binding minimum wages. Yet, with linear taxation in place, all employed workers can become better-off provided that the unemployed receive limited welfare support. With progressive taxation in place, the minimum wage may garner political support (i.e. a majority) even when the unemployed receive substantial welfare support despite potential opposition from the capitalists and the unemployed, as well as from the very-high ability workers whose net-of-taxes incomes decline.
Keywords: E21; E24; E64; H23; J23; 330; minimum wage; capital accumulation; redistribution; unemployment